6- La problématique marginaliste, l’idéologie et le devenir Rwandais - Darnaud, Michel (Africa Development, 1977)
Rwanda, situated in the « Great Lakes » region in the heart of black Africa, was subjected to an intensive and brutal colonization imposed on the various rival ethnic groups, the Bantu Hutu farmers, the Hamite Tutsi shepherds and the Twa Pygmies. In 1900, after centuries of isola tion from foreign influence, and most significantly from Arab traders, Rwanda began allowing Catholic missionaries from the Lake Victoria region in Uganda and Tanzania to enter the country. They « invaded Rwanda peacefully, it is true, but brought with them a new idelology which was to have a profoundly destructive effect on deep-rooted tra dition. Although the two systems existed on equal terms in theory, inevitably the supremacy of the white coloniser's Western ideology was soon established. German soldiers gradually settled down in the inter-Lake region at the beginning of the century and helped to push the frontiers of German East Africa as far as Rwanda, which became a German Protectorate. As a result of the First World War, the Ger mans were replaced by the Belgians, who obtained a mandate to rule Ruanda-Urundi until the time of Independence in 1962 ; Rwanda then once again became an autonomous country after half a century of colo nization. The principal ideological changes introduced in order to serve foreign interests were : the introduction of metal as a monetary means of exchange (the rupee) detrimental to the barter system with its net work of reciprocity and complementarity ; a new language, French, to replace the vernacular, Kinyarwanda ; a new religion, Catholicism, destroying the cult of ancestors and ancestral religions ; and, finally, the emergence of marginalization, a logical result of uprooting a popu lation by force as well as an expression of the various social groups' inability to adjust to the new, « imported » society. The main result those very changes considered positive by the Westener — the intro duction of hospitals, dispensaries, schools, villas, roads, communica tions, radio, newspapers as well as intensive and scientific agriculture producing new crops — has been a deterioration of traditional institu tions and customs. In the old days, the all-powerful king, the Mwami, had created an ideological system of social protection and mystique. The cult of the dead and the worshipping of ancestors left no room for transgression *or deviation, i. e. marginalization. The whole cultural universe, based on myths, legends and fairy tales, on exchange and reciprocity, on the social ceremonies marking births, marriages and deaths constituted the link between the Rwandan and his country. Colo nization, by setting up a new system of reference, i. e. acculturation, destroyed the integration/reference system by creating the conflict between tradition and modernity. Thus, colonization has nothing but negative effects, which explains the Rwandan people's uncertain future, faced as the country is with growing marginalization and generalized degradation.